Mini Review: Work-Life Balance, Psychological Structure, Employee Resilience, and Organization Commitment to Employee Wellbeing : Human Resource Management - Susanto, Primadi Candra; Supardi, Supardi; Henokh Parmenas, Naik; Tannady, Hendy; Panatap Soehaditama, Josua (Greenation Publisher & Yayasan Global Research National, 2023)
The purpose of this study is to find out what factors can influence the occurrence of employee welfare in the company, this article aims to examine and synthesize literature studies related to attitudes, Work-Life Balance; Psychological Structure; Employee Resilience; Organizational Commitment to behavioral events as well as to see the results of the research variables to be reviewed and whether there is influence between one variable and other variables partially and/or simultaneously. This study uses a literature review by looking for references related to variables from several international articles from science direct. This study provides an overview of the articles obtained by describing the influence between variables. The results of the research show that several variables influence the evidence of exposure in the matrix. The study of employee welfare in this literature summary article explicitly focuses on supporting variables that can accelerate employee welfare efficiently within a company, namely Work-Life Balance, Psychological Structure, Employee Resilience, and Organizational Commitment. The findings from the research are the formation of a new research framework that has not previously existed in previous studies.